Design optimization of implant geometrical characteristics enhancing primary stability using FEA of stress distribution around dental prosthesis. Issue 9 (11th August 2021) - Elleuch, Sameh; Jrad, Hanen; Kessentini, Amir; Wali, Mondher; Dammak, Fakhreddine
Abstract: The main objective of this study was to investigate the influence of implant geometrical characteristics: diameter, length and thread's pitch, on stress distribution around dental prosthesis. A set of numerical simulations using FEM were conducted and responses surfaces were generated. With the aim of optimizing the equivalent stresses responses; desirability function approach was adopted to solve this multi-objective problem. Results showed that implant diameter had most significant influence on generated stresses and high concentration of stresses were identified in the lower part of the implant. This study is helpful in choosing the optimal dental implant for clinical application.